Silent uterine rupture in second trimester: a differential diagnosis to remember - Mundhra, Rajlaxmi; Bahadur, Anupama; Kunwar, Kiran; Mishra, Juhi; Yadav, Ankita; Das, Debashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Spontaneous silent uterine rupture is a life-threatening emergency situation requiring immediate laparotomy. High index of suspicion is key to prevent maternal mortality as at times the presentation can be nonspecific. Authors herein present a case of spontaneous silent uterine rupture during second trimester of pregnancy wherein the diagnosis was initially missed. To the best of authors knowledge, only a few cases with spontaneous fundal second trimester uterine rupture have been recorded so far.